(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Retaining of surgical sponges or instruments in the abdomen during surgery usually menifest as abscess, abdomino cutaneous fistula with or without any definite symptoms during lifetime. A 22 years lady presented to us with persistant symptoms of foul smelling lochial discharge, fever and abdominal pain of about 3 months following caesarean section due to retained gauze into abdominal cavity. The condition is termed as textiloma or gauzoma (from surgical gauze). Several reports of textiloma were reported in literature but migration of retained gauze into terminal ileum without producing bowel symptom is not reported. It is an ethical surgical repercussions following caesarean section. JCMCTA 2014 ; 25 (2) : 69-72